Government crisis communication :exploring the use of selected media by the Department of Health during the COVID-19 Pandemic - Kanwendo, Mitchel Thendo (My University, 2025)
The purpose of this study was to explore government crisis communication through The National Department of Health on using selected media during the COVID-19 pandemic. This study used qualitative, exploratory approach to determine how The National Department of Health used Facebook and Twitter to disseminate messages of emergency to the citizens. This was to determine and explore the effectiveness of social media in reaching targeted masses in a short period of time in cases of emergency. The hubs of data collection for this study were posts made by The National Department of Health on Facebook and Twitter and comments by the public. Thematic content analysis was used to determine the themes that emerged from the selected media posts, while document analysis was used to analyse data. The selection of the posters was guided by the issues the researcher intended to study which reflected media use and media trust. The findings revealed that individuals relied on government’s social media for accurate information regarding the outbreak of the COVID-19 pandemic. This is proven by the engagement that was taking place between individuals on the comments section on every post the government released. The study therefore recommended that the Government should prioritise engagement on social media platforms. It was also suggested that the government should come up with be a response strategy to answer questions by the public in times of uncertainty
Thesis (M.A. (Communication Studies)) -- University of Limpopo, 2025
Keywords: COVID-19 pandemic; Facebook; Twitter; The Department of Health; Crisis communication.; Communication in crisis management; Communication; COVID-19 Pandemic, 2020-2023, in mass media; Social media